Identification of Micro Ribonucleic Acids and Their Targets in Response to Plasmodiophora brassicae Infection in Brassica napus - Li, Qian; Shah, Nadil; Zhou, Xueqing; Wang, Huiying; Yu, Wenlin; Luo, Jiajie; Liu, Yajun; Li, Genze; Liu, Chao; Zhang, Chunyu; Chen, Peng (Frontiers in Plant Science, 2021)
Clubroot disease, which is caused by the soil-borne pathogen Plasmodiophora brassicae War (P. brassicae), is one of the oldest and most destructive diseases of Brassica and cruciferous crops in the world. Plant microRNAs [micro ribonucleic acids (miRNAs)] play important regulatory roles in several developmental processes. Although the role of plant miRNAs in plant-microbe interaction has been extensively studied, there are only few reports on the specific functions of miRNAs in response to P. brassicae. This study investigated the roles of miRNAs and their targets during P. brassicae infection in a pair of Brassica napus near-isogenic lines (NILs), namely clubroot-resistant line 409R and clubroot-susceptible line 409S. Small RNA sequencing (sRNA-seq) and degradome-seq were performed on root samples of 409R and 409S with or without P. brassicae inoculation. sRNA-seq identified a total of 48 conserved and 72 novel miRNAs, among which 18 had a significant differential expression in the root of 409R, while only one miRNA was differentially expressed in the root of 409S after P. brassicae inoculation. The degradome-seq analysis identified 938 miRNA target transcripts, which are transcription factors, enzymes, and proteins involved in multiple biological processes and most significantly enriched in the plant hormone signal transduction pathway. Between 409R and 409S, we found eight different degradation pathways in response to P. brassicae infection, such as those related to fatty acids. By combining published transcriptome data, we identified a total of six antagonistic miRNA-target pairs in 409R that are responsive to P. brassicae infection and involved in pathways associated with root development, hypersensitive cell death, and chloroplast metabolic synthesis. Our results reveal that P. brassicae infection leads to great changes in miRNA pool and target transcripts. More interestingly, these changes are different between 409R and 409S. Clarification of the crosstalk between miRNAs and their targets may shed new light on the possible mechanisms underlying the pathogen resistance against P. brassicae.